Ultrasound-guided Brachial Plexus Block as a Sole Anaesthetic Technique in a Child for Fixation of Humerus Fracture: A Case Report - S Parthasarathy; Thalangara Mukhthar Abdulla (Journal of Clinical and Diagnostic Research, 2024)
Managing supracondylar fractures provides distinct problems in the complex setting of paediatric trauma. A 36-month-old male child was admitted with accidental injury and supracondylar fracture of left humerus. There were no other injuries. The child was planned open reduction and internal fixation in the right lateral position. The plan was to administer nerve block. To satisfactorily transfer the baby, the authors administered 5 mg of oral diazepam to the mother after explanation. The patient was smoothly transferred inside with syrup promethazine 5 mL. After securing an intravenous access, and an intravenous pethidine of 10 mg, he was administered ultrasound guided brachial plexus block with a supraclavicular approach with 5 mL of 0.5% bupivacaine. The pain subsided and the patient slept well. The surgery and the postoperative period were uneventful. The authors concluded that sedating the mother prior will help in separation and nerve blocks can be administered in children in precise sites with the help of ultrasound but without supplemental general anaesthesia. This report is the first case report to do without the use of any intravenous anaesthetic drugs.